17β-Estradiol Inhibits Proliferation and Oxidative Stress in Vascular Smooth Muscle Cells by Upregulating BHLHE40 Expression - Feng, Dan-dan; Zheng, Bin; Yu, Jing; Zhang, Man-li; Ma, Ying; Hao, Xiao; Wen, Jin-kun; Zhang, Xin-hua (Frontiers in Cardiovascular Medicine, 2021)
Background: Intimal hyperplasia is a major complication of restenosis after angioplasty. The abnormal proliferation and oxidative stress of vascular smooth muscle cells (VSMCs) are the basic pathological feature of neointimal hyperplasia. 17β-Estradiol can inhibit VSMCs proliferation and inflammation. However, it is still unclear whether and how 17β-Estradiol affects intimal hyperplasia. Methods: The neointima hyperplasia was observed by hematoxylin/eosin staining. The expression of PCNA, cyclin D1, NOX1, NOX4 and p47phox in neointima hyperplasia tissues and VSMCs was determined by qRT-PCR and Western blotting. MTS assay, cell counting and EdU staining were performed to detect cells proliferation. The oxidative stress was assessed by ROS staining. Results: 17β-Estradiol suppressed carotid artery ligation-induced intimal hyperplasia, which is accompanied by an increase of BHLHE40 level. Furthermore, loss- and gain-of-function experiments revealed that BHLHE40 knockdown promotes, whereas BHLHE40 overexpression inhibits TNF-α-induced VSMC proliferation and oxidative stress. 17β-Estradiol inhibited TNF-α-induced VSMC proliferation and oxidative stress by promoting BHLHE40 expression, thereby suppressing MAPK signaling pathways. In addition, enforcing the expression of BHLHE40 leads to amelioration of intimal hyperplasia. Conclusions: Our study demonstrates that 17β-Estradiol inhibits proliferation and oxidative stress in vivo and in vitro by promotion of BHLHE40 expression.